Academic motivation in undergraduate nursing students: an analytical cross-sectional study - Aslam, Muhammad Zeeshan; Ajani, Khairulnissa; Zahid, Wajeeha; Salim, Zeenar; Soomar, Salman Muhammad (Journal of the Pakistan Medical Association, 2025)
Objectives: To assess the motivation level of undergraduate nursing students, and to explore the factors that affect their academic motivation. Method: The analytical, cross-sectional study was conducted from September to December 2021 at Aga Khan University School of Nursing and Midwifery, Karachi, and comprised undergraduate nursing students enrolled in the four-year Bachelor of Science in Nursing programme. Data was collected using a self-developed questionnaire which explored the motivation level of the subjects. Data was analysed using SPSS 26. Results: Of the 233 subjects with mean age 21.1±1.56 years, 201(86.3%) were females, and 61(26.2%) were in the final year of the academic programme. Year I students had the highest mean motivation score 5.85±1.04, while final year students had the lowest score 5.66±1.23, and there was significant difference with respect to extrinsic motivation (p<0.05). Most students had joined the nursing profession because of their family’s wishes 97(41.6%). Conclusion: As motivation decreased in the final year, and the students were extrinsically motivated, faculty members’ role becomes vital in promoting intrinsic motivation through the use of different teaching-learning strategies. Key Words: Academic motivation, Undergraduate nursing students, Intrinsic motivation, Extrinsic motivation, Motivational factors.